2023
DOI: 10.3390/metabo13030341
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-B and Heavy Metal-Induced Regulation of Secondary Metabolites in Medicinal Plants: A Review

Abstract: Despite a rich history and economic importance, the potential of medicinal plants has not been fully explored under different abiotic stress conditions. Penetration of UV-B radiation and contamination of heavy metals are two important environmental stress for plants with remarkable influence on the defense-related and pharmaceutically important secondary metabolites of medicinal plants. UV-B and heavy metal contamination may become a critical issue that either positively or negatively affects the quality and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Moreover, even low Cd concentrations boosted their capacity for flavonoid accumulation, as shown for several plant organisms [178,179], and increased the polyphenolic pool in the plants of Vaccinium corybosum (Ericaceae family) [176] and Hypoxis hemerocallidea [179]. A similar trend was observed for callus cultures of Linum usitatissimum [57].…”
Section: Phenolic Antioxidants (Ao) and Their Role In Stress-coping S...supporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, even low Cd concentrations boosted their capacity for flavonoid accumulation, as shown for several plant organisms [178,179], and increased the polyphenolic pool in the plants of Vaccinium corybosum (Ericaceae family) [176] and Hypoxis hemerocallidea [179]. A similar trend was observed for callus cultures of Linum usitatissimum [57].…”
Section: Phenolic Antioxidants (Ao) and Their Role In Stress-coping S...supporting
confidence: 59%
“…It has been shown that MYB, bHLH, WRKY, and a few other stress-responsive plant transcription factors regulate the expression of genes involved in the phenolic compound biosynthesis [189]. It has been reported that, under abiotic stress, anthocyanin accumulation in the top layer of plant epidermal cells is activated by the stress-induced ROS signal transduction with subsequent transcription of the regulatory factors that activate anthocyanin biosynthesis gene expression [178,190]. It has been shown that MYB, bHLH, WRKY, and a few other stress-responsive plant transcription factors regulate the expression of genes involved in the phenolic compound biosynthesis [189].…”
Section: Phenolic Antioxidants (Ao) and Their Role In Stress-coping S...mentioning
confidence: 99%
“…Further investigation into the use of plant growth regulators, known to favor proliferation, is likely to lead to further stimulation of terpene biosynthesis, as has been shown in other aromatic plants, which may lead to beneficial changes in the quality and quantity of the produced secondary metabolites [ 119 ]. Furthermore, in vitro cultures are offered for research and introduction to the production process of the secondary metabolites via the use of UV-B radiation, as it has been shown to affect the production of essential oil and its components in plants [ 120 , 121 , 122 ].This study showed that greenhouse cultivation as well as in vitro culture can be a valid alternative for the production of plant material of C. nepeta subsp. spruneri characterized by the same aromatic flavor and providing a similar yield of essential oil and its constituents as plants grown in the field.…”
Section: Resultsmentioning
confidence: 99%
“…A significant worldwide concern is the release of HM into the ecosystem as a result of various anthropogenic activities. The growth of medicinal plants in soil enriched with HM can ultimately impact the biosynthesis of phytocompounds [25,26]. These HM is be responsible for a higher level of ROS generation.…”
Section: Mechanism Of Heavy Metals In Enhancement Of Phenolic Compoundmentioning
confidence: 99%